The Role of Campus Teaching Programs in Enhancing Junior High School Students' Numeracy and Literacy Skills - Akmal Suryadi; Inggrid Bella Pratama; Mega Cattleya P.A. Islami (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Kampus Mengajar is one of the programs of the Ministry of Education, Culture, Research and Technology that focuses on teaching activities that open up opportunities for students to dedicate their skills and knowledge in helping students in elementary and junior high schools, especially in underdeveloped areas. Based on data from the Ministry of Education and Culture, there are still many schools in underdeveloped areas that need teacher assistance to improve literacy and numeracy skills that are still low. The Kampus Mengajar program is implemented at SMP PSM Taji Magetan. Kampus Mengajar focuses on 3 things, namely improving literacy and numeracy, technology adaptation, and school administration. The results of the Kampus Mengajar work program are progress in literacy and numeracy, technological progress, and efficiency of school administration.